Effects of maternal-offspring supplementation of probiotics and synbiotics on the immunity of offspring Bama mini-pigs - Ding, Sujuan; Ye, Ting; Azad, Md. Abul Kalam; Zhu, Qian; Liu, Yating; Tan, Bie; Kong, Xiangfeng (Frontiers in Immunology, 2025)
Maternal nutrition is one of the main factors regulating the growth and immunity of piglets. This study aimed to investigate the effects of maternal or maternal-offspring supplementation of antibiotics, probiotics, and synbiotics on the immunity of offspring (21, 65, and 125 day-old) in Bama mini-pigs. The results showed that adding antibiotics to maternal diets increased the plasma IFN-γ level of offspring piglets at 21 day-old. Compared with maternal supplementation, maternal-offspring supplementation of antibiotics decreased the IL-10 level in the spleen, probiotics decreased IL-2, IL-10, and TNF-α levels in the ileum, and synbiotics decreased IL-10 and IFN-γ levels in the ileum of offspring piglets. Moreover, maternal-offspring antibiotics supplementation increased the IL-1β level in the ileum, while probiotics supplementation increased the IL-1β level in the spleen of offspring piglets. Maternal antibiotics supplementation increased the TNF-α level in the ileum at 95 day-old compared with maternal probiotics and synbiotics supplementation. Maternal-offspring antibiotics supplementation increased the IL-1β level in the ileum compared with the probiotics supplementation, while synbiotics supplementation increased the IL-6 level in the ileum than the probiotics and antibiotics supplementation at 95 day-old. Moreover, maternal-offspring probiotics supplementation increased the IL-1β level in the spleen of offspring pigs, which was higher than the maternal probiotics supplementation. These findings suggest that the immune function of the offspring piglets varied depending on the specific approach used for probiotics and synbiotics supplementation.